Binding Protein - Abdelmohsen, Kotb (IntechOpen, 2012)
Proteins are essential for all cellular events. They bind or interact with additional players such as other proteins, peptides, DNA, and RNA to exert their functions. Revealing protein binding partners is important in understanding the mechanisms through which they function in the cells and the organism. These interactions are essential in the regulation of cell fates and could be important in drugs development. For example proteins can bind mRNA to regulate stability and translation. They also bind other proteins for degradation or proteolysis. These mRNAs and proteins could be involved in cellular processes such as cell survival or apoptosis. This book contains review articles dealing with protein interactions with the above mentioned factors. The enclosed articles could be informative and stimulating for readers interested in protein binding partners and the consequences of such interactions.